Thermal Performance Evaluation of the Variation of Condenser Dimensions for Foodstuffs Transportation Cooling Systems - I Gede Bawa Susana; I Gede Santosa (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
The process of sending food using transportation requires a refrigeration system to keep the product fresh. Unsuitable temperatures will cause the transported products to often experience damage so that they are rejected in the mark. To achieve this, it is done through testing using a condenser with several variations of dimensions for a room temperature of 5oC. The dimensions of condenser-1 are (W 23 x H 14) inch2 x 19 mm, condenser-2 is (W 23 x H 14) inch2 x 26 mm, and condenser-3 is (W 23 x H 14) inch2 x 44 mm. The test results show that condenser-3 produces a faster cooling time compared to condenser-2 and condenser-1. Cooling time for condenser-3 is 1160 minutes, while condenser-2 and condenser-1 are 1560 minutes and 1860 minutes, respectively. Condenser-3 provides the lowest compression work of 42.131 kJ/kg compared to condensers 2 and 1, respectively 42.931 kJ/kg, and 46.147 kJ/kg. This has an impact on the COP value, namely condenser-3, condenser-2, and condenser-1 each of 3.437, 3.233, and 2.845. COP at condenser-3 occurs the highest. These results indicate that the largest condenser dimension gives the most optimum thermal performance results. An efficient refrigeration system has low compression work and high COP.